Polyvinyl chloride control cable
By using composite structures and combinations of ceramic silicone rubber and flame-retardant silicone rubber materials in the cable, the problem of insufficient flame retardant performance of existing cables is solved, and efficient flame retardant and heat insulation effects are achieved, meeting the fire protection requirements of subway projects .
Patent Information
- Application Number
- CN202411610637.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The flame retardant performance of existing cables is insufficient, making it difficult to meet the requirements of subway projects for safe and reliable fire-proof cables.
The structure is adopted, which is arranged in sequence from the inside to the outside, a water-blocking belt layer, an insulated inner sheath, a flame-retardant winding belt layer, a flame-retardant inner sheath, a metal sheath layer and an outer sheath, combined with ceramics The use of silicone rubber and flame-retardant silicone rubber materials form a double flame-retardant protection.
It significantly improves the flame retardant performance of the cable, can form a hard protective layer at high temperatures, delay the spread of fire, protect the internal structure of the cable, and meets the B1 level combustion characteristics and subway fire protection standards.
Smart Images

Figure CN119480257A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of power cables, and in particular to a polyvinyl chloride control cable. Background Art
[0002] Control cables are PVC insulated and PVC sheathed control cables suitable for industrial and mining enterprises, energy and transportation departments, and for control and protection of lines with an AC rated voltage of less than 450 / 750 volts. Control cables are moisture-proof, corrosion-resistant and damage-resistant, and can be laid in tunnels or cable trenches. Power cables are used to transmit and distribute high-power electrical energy in the main lines of power systems. Control cables transmit electrical energy directly from the distribution points of the power system to the power connection lines of various electrical equipment and appliances. The rated voltage of power cables is generally 0.6 / 1kV and above, and the rated voltage of control cables is mainly 450 / 750V. When power cables and control cables of the same specifications are produced, the insulation and sheath thickness of power cables are thicker than those of control cables.
[0004] The Chinese invention with announcement number CN214847867U discloses a polyvinyl chloride control cable, comprising a composite cable core, a wrapping tape layer, an inner sheath, a metal braided layer and a wear-resistant outer layer arranged in sequence from the inside to the outside; the wrapping tape layer is a ceramic silicone rubber wrapping tape wrapped around the composite cable core; the wear-resistant outer layer is a nylon material extruded and covered on the metal braided layer.
[0005] However, the flame retardant performance of existing cables is ordinary and it is difficult to meet the requirements of fire resistance and flame retardant performance. In order to adapt to the favorable market situation of rapid development of subway construction and provide safe and reliable fireproof cables for subway projects, it is urgent to conduct in-depth research and innovative improvements on cable materials and cable structures. Summary of the invention
[0006] In order to overcome the above technical defects, the present invention provides a polyvinyl chloride control cable.
[0007] In order to solve the above problems, the present invention is implemented according to the following technical solutions:
[0008] The polyvinyl chloride control cable of the present invention is characterized by comprising a composite cable core, a water-blocking wrapping tape layer, an insulating inner sheath, a flame-retardant wrapping tape layer, a flame-retardant inner sheath, a metal sheath layer and an outer sheath which are sequentially arranged from the inside to the outside;
[0009] The flame retardant wrapping tape layer is a ceramic silicone rubber tape wrapped around the insulating inner sheath;
[0010] The flame retardant inner sheath is made of flame retardant silicone rubber material extruded and covered on the water-blocking wrapping tape layer.
[0011] Preferably, the flame retardant silicone rubber material comprises the following components in parts by weight:
[0012] 90 parts of polymethylvinylsiloxane;
[0013] 56 parts of silicon dioxide;
[0014] 6 parts of hydroxy siloxane;
[0015] 10 parts of calcium silicate;
[0016] 16 parts of composite flame retardant;
[0017] 1 part of hydrogen siloxane;
[0018] 1 part of platinum vulcanizing agent.
[0019] Preferably, the composite flame retardant is a mixture of inorganic hydroxide, antimony trioxide and magnesium aluminum carbonate hydrotalcite, and the mass ratio of the inorganic hydroxide, antimony trioxide and magnesium aluminum carbonate hydrotalcite is 5:1:3.
[0020] Preferably, the insulating inner sheath is a ceramic silicone rubber material extruded and covered on the water-blocking wrapping tape layer.
[0021] Preferably, the ceramic silicone rubber material comprises the following components in parts by weight:
[0022] α,ω-hydroxy-terminated polydimethylsiloxane 80 parts;
[0023] 40 parts of fumed silica;
[0024] 20 parts of modified nano clay;
[0025] 6 parts of 500 viscosity silicone oil;
[0026] 10 parts of composite flame retardant;
[0027] 20 parts of porcelain powder;
[0028] 1 part of cross-linking aid;
[0029] 1 part of platinum vulcanizing agent.
[0030] Preferably, the modified nano-clay is prepared by the following method:
[0031] (1) Mixing raw materials: mixing nano clay with aminopropyl triethoxy silane to obtain a mixture; wherein the amount of aminopropyl triethoxy silane is 3-5% of the mass of the nano clay;
[0032] (2) Heating and stirring: heating the mixture to 50-60° C. and stirring continuously for 20-30 minutes;
[0033] (3) Adding nano-silicon dioxide: Add 1.5% of the total mass of the mixture to the heated and stirred mixture;
[0034] (4) High-speed dispersion: The mixture with nano-silicon dioxide added is subjected to high-speed dispersion treatment to obtain modified nano-clay.
[0035] Preferably, the metal sheath layer is a corrugated aluminum sheath.
[0036] Preferably, the composite cable core comprises a plurality of insulating cores, each of which comprises a conductor and an insulating layer wrapping the outer surface of the conductor;
[0037] Wherein, the insulating layer is a polyvinyl chloride sheath material extruded on the conductor.
[0038] Preferably, the conductor is the first conductor structure or the second conductor structure in GB / T 3956.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The present invention provides a polyvinyl chloride control cable, comprising a composite cable core, a water-blocking wrapping tape layer, an insulating inner sheath, a flame-retardant wrapping tape layer, a flame-retardant inner sheath, a metal sheath layer and an outer sheath, which are arranged in sequence from the inside to the outside. The flame-retardant wrapping tape layer is a ceramic silicone rubber tape wrapped on the insulating inner sheath. The flame-retardant inner sheath is a flame-retardant silicone rubber material extruded and covered on the water-blocking wrapping tape layer.
[0041] 1. The cable of this product is equipped with a ceramic silicone rubber wrapping tape layer, which has excellent flame retardant properties and low heat generation when burned. The ceramic material used can form a hard protective layer at a high temperature above 350°C, with honeycomb-shaped holes inside, which can provide a good heat insulation effect. At the same time, the material has good crusting performance during heating, no dripping, and good low smoke performance.
[0042] 2. This product adopts the combined technology of flame-retardant wrapping tape layer and flame-retardant inner sheath. The flame-retardant inner sheath is a flame-retardant silicone rubber material extruded and covered on the water-blocking wrapping tape layer. This material does not contain halogen, has low smoke production when burning, and has good flame-retardant effect. It provides double flame-retardant protection. The ceramic silicone rubber tape forms a hard ceramic-like protective layer at high temperature, and combined with the flame-retardant silicone rubber, it provides excellent flame-retardant and heat-insulating effects. This combined structural design allows the cable to remain undamaged for a long time in the event of a fire, delays the spread of fire, and protects the internal structure of the cable. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The specific embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings, wherein:
[0044] Figure 1It is a cross-sectional schematic diagram of a polyvinyl chloride control cable of the present invention;
[0045] In the figure:
[0046] 10- conductor;
[0047] 20-insulating layer;
[0048] 30-water blocking wrapping tape layer;
[0049] 40-insulating inner sheath;
[0050] 50-flame retardant wrapping tape layer;
[0051] 60-flame retardant inner sheath;
[0052] 70-metal sheath layer;
[0053] 80-Outer sheath. DETAILED DESCRIPTION
[0054] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0055] The flame retardant performance of existing cables is ordinary and it is difficult to meet the requirements of fire resistance and flame retardant performance. In order to adapt to the favorable market situation of rapid development of subway construction and provide safe and reliable fireproof cables for subway projects, it is urgent to conduct in-depth research and innovative improvements on cable materials and cable structures.
[0056] Therefore, the present invention provides a polyvinyl chloride control cable for subway. Figure 1 As shown, the preferred structure of a polyvinyl chloride control cable described in the present invention.
[0057] Embodiment 1
[0058] like Figure 1 As shown, the polyvinyl chloride control cable described in the present invention comprises a composite cable core, a water-blocking wrapping tape layer, an insulating inner sheath, a flame-retardant wrapping tape layer, a flame-retardant inner sheath, a metal sheath layer and an outer sheath arranged in sequence from the inside to the outside. The flame-retardant wrapping tape layer is a ceramic silicone rubber tape wrapped on the insulating inner sheath. The flame-retardant inner sheath is a flame-retardant silicone rubber material extruded and covered on the water-blocking wrapping tape layer.
[0059] The main innovations of the present invention are as follows:
[0060] 1. The cable of this product is equipped with a ceramic silicone rubber wrapping tape layer, which has excellent flame retardant properties and low heat generation when burned. The ceramic material used can form a hard protective layer at a high temperature above 350°C, with honeycomb-shaped holes inside, which can provide a good heat insulation effect. At the same time, the material has good crusting performance during heating, no dripping, and good low smoke performance.
[0061] 2. This product adopts the combined technology of flame-retardant wrapping tape layer and flame-retardant inner sheath. The flame-retardant inner sheath is a flame-retardant silicone rubber material extruded and covered on the water-blocking wrapping tape layer. This material does not contain halogen, has low smoke production when burning, and has good flame-retardant effect. It provides double flame-retardant protection. The ceramic silicone rubber tape forms a hard ceramic-like protective layer at high temperature, and combined with the flame-retardant silicone rubber, it provides excellent flame-retardant and heat-insulating effects. This combined structural design allows the cable to remain undamaged for a long time in the event of a fire, delays the spread of fire, and protects the internal structure of the cable.
[0062] In a preferred embodiment, the flame retardant silicone rubber material comprises the following components in parts by weight:
[0063] 90 parts of polymethylvinylsiloxane;
[0064] 56 parts of silicon dioxide;
[0065] 6 parts of hydroxy siloxane;
[0066] 10 parts of calcium silicate;
[0067] 16 parts of composite flame retardant;
[0068] 1 part of hydrogen siloxane;
[0069] 1 part of platinum vulcanizing agent.
[0070] In a specific implementation, the composite flame retardant is a mixture of inorganic hydroxide, antimony trioxide and magnesium aluminum carbonate hydrotalcite, and the mass ratio of the inorganic hydroxide, antimony trioxide and magnesium aluminum carbonate hydrotalcite is 5:1:3. By using the composite flame retardant, the rubber oxygen index of the product can reach above 36.
[0071] In the flame retardant silicone rubber material of the present invention, polymethylvinylsiloxane is used as the base material in the material and as the main strength component. Silicon dioxide is used as a reinforcing material to improve the tensile and tearing strength of the material. Hydroxylsiloxane is used as an auxiliary agent to increase the adhesion between polymethylvinylsiloxane and silicon dioxide components. The purpose of adding calcium silicate is to burn the crust and prevent dripping.
[0072] The flame retardant silicone rubber material of the present invention meets the B1 level combustion characteristics, and the product performance test results are as follows:
[0073] (1) Vertical combustion: Tested according to GB / T10707-2008, sample size is 130 mm × 13 mm × 3 mm.
[0074] (2) Vitrification strength: tested according to GB / T6569-2006, using a three-point bending fixture, a span of 40 mm, and a beam movement rate of 0.5 mm / min. The bending strength of the test sample is used as its vitrification strength. Five samples are tested in parallel and the median value is taken. The sample size is 70 mm × 6 mm × 4 mm. It is placed in a high-temperature box furnace and heated to the target temperature at 3 °C / min. The temperature is kept for a certain period of time and then naturally cooled to room temperature and taken out.
[0075] After testing, the product performance is shown in Table 1 and Table 2:
[0076] Table 1 Vertical combustion test results of flame retardant silicone rubber materials
[0077]
[0078] Table 2 Performance test results of flame retardant silicone rubber materials
[0079]
[0080] In a preferred embodiment, the insulating inner sheath is a ceramic silicone rubber material extruded and covered on the water-blocking wrapping tape layer. Specifically, the ceramic silicone rubber material includes the following components in parts by weight:
[0081] α,ω-hydroxy-terminated polydimethylsiloxane 80 parts;
[0082] 40 parts of fumed silica;
[0083] 20 parts of modified nano clay;
[0084] 6 parts of 500 viscosity silicone oil;
[0085] 10 parts of composite flame retardant;
[0086] 20 parts of porcelain powder;
[0087] 1 part of cross-linking aid;
[0088] 1 part of platinum vulcanizing agent.
[0089] In a specific implementation, the composite flame retardant is a mixture of inorganic hydroxide, antimony trioxide and magnesium aluminum carbonate hydrotalcite, and the mass ratio of the inorganic hydroxide, antimony trioxide and magnesium aluminum carbonate hydrotalcite is 5:1:3. By using the composite flame retardant, the rubber oxygen index of the product can reach above 36.
[0090] In a specific implementation, the modified nano-clay is prepared by the following method:
[0091] (1) Mixing raw materials: mixing nano clay with aminopropyl triethoxy silane to obtain a mixture; wherein the amount of aminopropyl triethoxy silane is 3-5% of the mass of the nano clay;
[0092] (2) Heating and stirring: heating the mixture to 50-60° C. and stirring continuously for 20-30 minutes;
[0093] (3) Adding nano-silicon dioxide: Add 1.5% of the total mass of the mixture to the heated and stirred mixture;
[0094] (4) High-speed dispersion: The mixture with nano-silicon dioxide added is subjected to high-speed dispersion treatment to obtain modified nano-clay.
[0095] In the present invention, the modified nanoclay can significantly improve the hardness, strength and toughness of the material due to the nano-level dispersion and surface modification. The performance of the nanoclay composite material at high temperature is improved, including the improvement of hardness and strength. Pressure resistance and impact resistance: The modified nanoclay enhances the barrier and air tightness of the material, and has good pressure resistance and impact resistance. Heat sealing performance: It has the characteristics of high heat sealing strength and good heat sealing performance.
[0096] The ceramic silicone rubber material of the present invention meets the B1 level combustion characteristics, and the product performance test results are as follows:
[0097] (1) Vertical combustion: Tested according to GB / T10707-2008, sample size is 130 mm × 13 mm × 3 mm.
[0098] (2) Vitrification strength: tested according to GB / T6569-2006, using a three-point bending fixture, a span of 40 mm, and a beam movement rate of 0.5 mm / min. The bending strength of the test sample is used as its vitrification strength. Five samples are tested in parallel and the median value is taken. The sample size is 70 mm × 6 mm × 4 mm. It is placed in a high-temperature box furnace and heated to the target temperature at 3 °C / min. The temperature is kept for a certain period of time and then naturally cooled to room temperature and taken out.
[0099] After testing, the product performance is shown in Table 3 and Table 4:
[0100] Table 3 Vertical combustion test results of ceramic silicone rubber materials
[0101]
[0102] Table 4 Performance test results of ceramic silicone rubber materials
[0103]
[0104] In a specific implementation, the metal sheath layer is a corrugated aluminum sheath.
[0105] In a specific implementation, the composite cable core includes a plurality of insulating cores, each of which includes a conductor and an insulating layer wrapping the outer surface of the conductor;
[0106] Wherein, the insulating layer is a polyvinyl chloride sheath material extruded on the conductor.
[0107] In a specific implementation, the water-blocking wrapping tape layer is formed by wrapping the water-blocking tape. The gaps in the composite cable core are filled with water-blocking yarns.
[0108] Specifically, the conductor is the first conductor structure or the second conductor structure in GB / T 3956.
[0109] In a preferred implementation, the outer sheath is made of ceramic silicone rubber material.
[0110] The present invention verifies the performance of products of polyvinyl chloride control circuits, tests the insulation and sheath mechanical properties and insulation electrical properties of the products, and performs short-circuit integrity tests on insulated wire cores, fire resistance tests and combustion tests on finished cables.
[0111] (1) The control cable was subjected to a 3000V×5min withstand voltage test, the insulated wire core was subjected to a 2500V×5min water immersion withstand voltage test, and a 168h water immersion insulation resistance retention test. The test data are as follows: withstand voltage test: no breakdown. Water immersion withstand voltage test: no breakdown. After 168h of immersion, the insulation resistance retained 90%, which is similar to that of cross-linked polyethylene materials.
[0112] It can be seen that the water-immersion insulation resistance retention rates of the silicone rubber material of the present invention and the cross-linked polyethylene are very close, indicating that the silicone rubber has a strong ability to resist moisture.
[0113] (2) The test equipment is used to simulate the stable large current required when the test cable is short-circuited, so that the conductor melts within 3 seconds after power is turned on. The test is carried out at (25±5)℃. The sample is placed in the test environment for at least 24 hours. Cut an insulated wire core with a length of (200±5)mm, and strip 30 to 35mm of insulation at both ends, and fix the two ends to the current terminals of the test device respectively. Turn on the power switch of the test equipment and observe the fuse of the insulated wire conductor being tested or the high temperature fire of the insulation. When the above situation occurs, the power switch should be turned off immediately to ensure the safety of the test equipment.
[0114] The test results show that when the conductor of the insulated wire core sample in this work is short-circuited and melted, the insulation layer remains intact and no cracking or fire occurs.
[0115] (3) B1 flame retardant property requirements. Comprehensive combustion performance tests were conducted on the two materials and cable products made of these materials. The test results are shown in Table 5.
[0116] Table 5 Test results of combustion performance of finished cables
[0117] It can be seen from Table 5 that the performance of the control cable meets the requirements of GB 51298-2018 "Subway Design Fire Protection Standard" for power control lines in fire protection situations.
[0118]
[0119] For other structures of the polyvinyl chloride control cable described in this embodiment, refer to the prior art.
[0120] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Therefore, any modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention shall still fall within the scope of the technical solution of the present invention.
Claims
1. A polyvinyl chloride control cable, characterized in that: It includes a composite cable core, a water-blocking wrapping tape layer, an insulating inner sheath, a flame-retardant wrapping tape layer, a flame-retardant inner sheath, a metal sheath layer and an outer sheath which are arranged in sequence from the inside to the outside; The flame retardant wrapping tape layer is a ceramic silicone rubber tape wrapped around the insulating inner sheath; The flame retardant inner sheath is made of flame retardant silicone rubber material extruded and covered on the water-blocking wrapping tape layer.
2. The polyvinyl chloride control cable according to claim 1, characterized in that: The flame retardant silicone rubber material comprises the following components in parts by weight: 90 parts of polymethylvinylsiloxane; 56 parts of silicon dioxide; 6 parts of hydroxy siloxane; 10 parts of calcium silicate; 16 parts of composite flame retardant; 1 part of hydrogen siloxane; 1 part of platinum vulcanizing agent.
3. The polyvinyl chloride control cable according to claim 2, characterized in that: The composite flame retardant is a mixture of inorganic hydroxide, antimony trioxide and magnesium aluminum carbonate hydrotalcite, and the mass ratio of the inorganic hydroxide, antimony trioxide and magnesium aluminum carbonate hydrotalcite is 5:1:
3.
4. The polyvinyl chloride control cable according to claim 1, characterized in that: The insulating inner sheath is a ceramic silicone rubber material extruded and covered on the water-blocking wrapping tape layer.
5. The polyvinyl chloride control cable according to claim 4, characterized in that: The ceramic silicone rubber material comprises the following components in parts by weight: α,ω-hydroxy-terminated polydimethylsiloxane 80 parts; 40 parts of fumed silica; 20 parts of modified nano clay; 6 parts of 500 viscosity silicone oil; 10 parts of composite flame retardant; 20 parts of porcelain powder; 1 part of cross-linking aid; 1 part of platinum vulcanizing agent.
6. The polyvinyl chloride control cable according to claim 5, characterized in that: The modified nano clay is prepared by the following method: (1) Mixing raw materials: mixing nano clay with aminopropyl triethoxy silane to obtain a mixture; wherein the amount of aminopropyl triethoxy silane is 3-5% of the mass of the nano clay; (2) Heating and stirring: heating the mixture to 50-60° C. and stirring continuously for 20-30 minutes; (3) Adding nano-silicon dioxide: Add 1.5% of the total mass of the mixture to the heated and stirred mixture; (4) High-speed dispersion: The mixture with nano-silicon dioxide added is subjected to high-speed dispersion treatment to obtain modified nano-clay.
7. The polyvinyl chloride control cable according to claim 1, characterized in that: The metal sheath layer is a corrugated aluminum sheath.
8. The polyvinyl chloride control cable according to claim 1, characterized in that: The composite cable core comprises a plurality of insulating cores, each of which comprises a conductor and an insulating layer wrapping the outer surface of the conductor; Wherein, the insulating layer is a polyvinyl chloride sheath material extruded on the conductor.
9. The polyvinyl chloride control cable according to claim 8, characterized in that: The conductor is the first conductor structure or the second conductor structure in GB / T 3956.
Citation Information
Patent Citations
Environment-friendly low-smoke low-halogen flame-retardant cable sheath material and preparation method thereof
CN112280205A
Fireproof polyvinyl chloride insulation control cable
CN214847867U
Bending-resistant cable
CN217008716U